Anti-basal ganglia antibodies and Tourette's syndrome: a voxel-based morphometry and diffusion tensor imaging study in an adult population. Issue 7 (26th February 2008) - Martino, D; Draganski, B; Cavanna, A; Church, A; Defazio, G; Robertson, M M; Frackowiak, R S J; Giovannoni, G; Critchley, H D
Abstract : Anti-basal ganglia antibodies (ABGAs) have been suggested to be a hallmark of autoimmunity in Gilles de la Tourette's syndrome (GTS), possibly related to prior exposure to streptococcal infection. In order to detect whether the presence of ABGAs was associated with subtle structural changes in GTS, whole-brain analysis using independent sets of T1 and diffusion tensor imaging MRI-based methods were performed on 22 adults with GTS with (n = 9) and without (n = 13) detectable ABGAs in the serum. Voxel-based morphometry analysis failed to detect any significant difference in grey matter density between ABGA-positive and ABGA-negative groups in caudate nuclei, putamina, thalami and frontal lobes. These results suggest that ABGA synthesis is not related to structural changes in grey and white matter (detectable with these methods) within frontostriatal circuits.